Cells, aging, and human disease - Fossel, Michael (OUP E-Books., 2004)
"Cells, Aging, and Human Disease examines aging from genes to clinical application, analyzing the cellular changes that underlie human age-related disease. The text explores both the fundamental processes of human aging and tissue-by-tissue pathology, as it details current research and state-of-the-art clinical interventions in aging and age-related disease." "Emphasizing human cell mechanisms, the first section of the book presents and analyzes our current knowledge of telomere biology and cell senescence. The text brings the reader up-to-date on telomere maintenance and dynamics. It explains both the limited and general model of cell senescence as the central component in human clinical aging."--Jacket.